2020
DOI: 10.1080/1023666x.2020.1827859
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying CTFE content in FK-800 using ATR-FTIR and time to peak crystallization

Abstract: Stripping MethodologyTATB is not appreciably soluble in ethyl acetate whereas FK-800 dissolves readily. To strip binder from PBX 9502 prills, the prills were placed in ethyl acetate, stirred, and allowed to dissolve. The TATB was allowed to settle and the remaining solution was decanted off. These steps were repeated as needed until a loose yellow powder (TATB) was observed. The solution of FK-800 and ethyl acetate was a clear, pale yellow indicating the presence of residual TATB. This solution was then pipett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, the band intensity of the anti‐symmetric stretch at the 1160 cm –1 obtained in the crystalline region is weaker than that obtained in the amorphous region. Kelly and co‐workers [ 31 ] have found that the C–F 2 symmetrical stretch strength is unrelated to the CTFE amount, while the anti‐symmetric stretch strength decreases with the increase of the CTFE amount. Therefore, similar results obtained in this study and literature indicate that the CTFE segment is the composition of the crystal region in the ultrathin film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the band intensity of the anti‐symmetric stretch at the 1160 cm –1 obtained in the crystalline region is weaker than that obtained in the amorphous region. Kelly and co‐workers [ 31 ] have found that the C–F 2 symmetrical stretch strength is unrelated to the CTFE amount, while the anti‐symmetric stretch strength decreases with the increase of the CTFE amount. Therefore, similar results obtained in this study and literature indicate that the CTFE segment is the composition of the crystal region in the ultrathin film.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3, P(VDF-CTFE) has characteristic absorption bands at 1160 cm -1 (anti-symmetric stretching vibration of the C-F 2 group), 1120 cm -1 (the symmetric stretching vibration of the C-F 2 group), and 962 cm -1 (the stretching vibration of the C-Cl group). [30,31] According to the molecular structure of P(VDF-CTFE), the band at 962 cm -1 can be regarded as the characteristic peak of the CTFE segment in P(VDF-CTFE).…”
Section: Crystalline State and Distribution Of Crystalline Nanostruct...mentioning
confidence: 99%
“…Each specimen is labeled with the injection order number and stored in a sealed container within a freezer to reduce crystallization and moisture exposure before testing. 7 Tensile testing is performed with an Instron 5569 with oven at a constant 40 C with a load cell of 2 kN and head speed of 500 mm/min. The oven has a testing strain limit of 178.50 mm or 521.47% of the original specimen length before the grip collides with the inside oven ceiling, which automatically terminates the test.…”
Section: Methodsmentioning
confidence: 99%
“…Specimen length, width, height, and flash measurements are recorded. Each specimen is labeled with the injection order number and stored in a sealed container within a freezer to reduce crystallization and moisture exposure before testing 7 …”
Section: Methodsmentioning
confidence: 99%